Robust Exponential Stability of Impulsive Stochastic Neural Networks with Leakage Time-Varying Delay - Chunge Lu; Linshan Wang (Abstract and Applied Analysis)
This paper investigates mean-square robust exponential stability of the equilibrium point of stochastic neural networks with leakage time-varying delays and impulsive perturbations. By using Lyapunov functions and Razumikhin techniques, some easy-to-test criteria of the stability are derived. Two examples are provided to illustrate the efficiency of the results.